Detection of Decaying Aroma of Salak Pondoh (Salacca edulis reinw) in Fifteen Days Storage at Room Temperature - Dika Intan Ayudiaswati; Anang Mohamad Legowo; Ahmad Ni'matullah Al-Baarri; Mulyana Hadipernata; Wisnu Broto; Risfaheri Risfaheri (Dept. Food Technology, Faculty of Animal and Agricultural Sciences, Diponegoro University, 2018)
Salak pondoh (Salacca edulis reinw) is one of horticulture product that easily to decay. Decaying aroma is one of indicators for qualities loss of salak pondoh. The purpose of this research is to detect the decay aroma of salak pondoh during the storage of 15 days. The preservation was categorized into three stages of preservation time: early, middle, and last day. All salak was preserved in room temperature at aseptic condition with detected humidity at 50-60%. According to the obtained data, it was detected that decay aroma was detected in 80% of salak in last stage of preservation. Amazingly, 5% of salak at this stage was not detected its decay aroma. As conclusion, decay of salak could be determined by the decay aroma and mostly it was appeared in the last stage of preservation.